(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
One of the most pressing problems in medicine today is the growth of immune-dependent pathologies, i.e. diseases based on immunopathological mechanisms [1, 7]. Primary immunodeficiencies are a large group of severe, genetically determined diseases, the cause of which is a violation of the body’s immune response cascade [2, 4]. Diseases with immunopathological conditions are characterized by early chronicity, reluctance to traditional methods of therapy and the need for immunorehabilitation [1]. This article is devoted to studying the problem of diagnosis and treatment of primary immunodeficiencies, with the aim of reducing the mortality of patients and improving their quality of life.